ChemInform Abstract: Design and Synthesis of Organic—Inorganic Hybrid Capsules for Biotechnological Applications. Issue 38 (10th September 2014) - Shi, Jiafu; Jiang, Yanjun; Wang, Xiaoli; Wu, Hong; Yang, Dong; Pan, Fusheng; Su, Yanlei; Jiang, Zhongyi
Abstract Review: 50 refs.